3(2x-2)=4(x+3)+4x

Simple and best practice solution for 3(2x-2)=4(x+3)+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-2)=4(x+3)+4x equation:



3(2x-2)=4(x+3)+4x
We move all terms to the left:
3(2x-2)-(4(x+3)+4x)=0
We multiply parentheses
6x-(4(x+3)+4x)-6=0
We calculate terms in parentheses: -(4(x+3)+4x), so:
4(x+3)+4x
We add all the numbers together, and all the variables
4x+4(x+3)
We multiply parentheses
4x+4x+12
We add all the numbers together, and all the variables
8x+12
Back to the equation:
-(8x+12)
We get rid of parentheses
6x-8x-12-6=0
We add all the numbers together, and all the variables
-2x-18=0
We move all terms containing x to the left, all other terms to the right
-2x=18
x=18/-2
x=-9

See similar equations:

| 2x²+7x-10=0 | | 2(x-4)-3(x+1)=5x+5 | | 9x+48=4x+3 | | -2/3=7/4-b | | x-24+89+x=180 | | 5w-8+2(4w+4)=-3(w+4) | | 15+9=-3(6x-8) | | 2m+1=7m-9 | | 0.6e-6=-0.40(e-10)-7 | | 19x-18=-170 | | 2(3x+7)=-33+29 | | 3(4n-1)-4=7n+3 | | 9(2x-3)=5x+17 | | 9. 6(x–3)+4=22 | | 20x+2=9x+6 | | 8x+14=6x+20 | | 0.6-6=-0.40(e-10)-7 | | 3(x+6)2(3x-4)=-50 | | /0.3y+0.18=1.5y-0.42 | | 2x+9+7=x+12 | | 10q−q−3q+6q=–16 | | 3(x-4)-7=-3(-8x+1)-7x | | 9/5x+3/2x=-33/10 | | (3x-22)+x=180=80+x+x | | 10q−–q-–3q+–6q=–16 | | 3(x-4)-7=-3(-8+1)-7x | | -10x-5=95 | | 5x/4+5=15/2 | | 6(6y+5)-24=3(4y+1)+3 | | 62.10=20+.5x+.15(20+5x | | -7x-33=-2(x+9) | | 10h+2h+3h-9h+2h=16 |

Equations solver categories